Self-Stigma in Individuals with Hash and Heroin use Disorders in Pakistan - Ghazala FazalDad, Seema Gul, Tamkeen Saleem (Pakistan Journal of Clinical Psychology, 2018)
Objectives: The present study examined experiences of self-stigma in individuals of substance use disorders (SUDs) after detoxification. The objective of the present study was to explore the differences between hash and heroin addicts about the experiences of self-stigma. Design of Study: Cross sectional study Place and Duration of Study: International Islamic University Islamabad from Sep 2014 to Jan 2015. Subjects & Method: Patients (N=150) from eight residential and outpatient substance abuse rehabilitation centers done the questionnaires focusing on demographic variables and stigma related experiences via demographic sheet and Substance Abuse Self Stigma Scale. The patients were addicts of hash (n=75) and heroin (n=75). For the statistical analysis descriptive, t-test and one way Anova were used. Results and Conclusion: The findings of the present study indicated that selfstigma is higher in individuals with heroin use disorder as compared to individuals with hash use disorder. Findings provided that there is no difference in experiences of self-stigma in patients in which family history of substance use was present and in those who did not have the family history of the substance abuse. It was also found that persons with SUDs with higher education had higher sense of self-stigma as compared to the lesser educated or illiterate persons with substance use.